Environmental Management Indicators: Instrument to Measure the Environmental Quality of the Universidad Nacional de Costa Rica - Chavarría-Solera, Fabián (2015)
In the present study; four environmental indicators relating to the daily work at the Universidad Nacional de Costa Rica (National University of Costa Rica) were quantified and systematized. A baseline was established in 2011 and from it environmental measures were raised and carried out to achieve the objectives and goals to prevent; reduce; restore or compensate the negative environmental impact that is happening. Specifically; the objective of this study was to verify the behavior of the institutional demand for electrical power; water; fossil fuel and paper for the period 2011-2014 and determine if the improvement actions implemented were effective. Monthly data used in the analysis were supplied by multiple internal and external stakeholders of each Campus; Facility and Station; then added up to obtain annual total values. These values were divided by the university population also to obtain per capita indicators. The main result is that each year at per capita level; the amount of these resources consumed by the institution continually decreases. The results seem to be a reflection of improvements in the implementation of policies and actions that integrate the entire university population - staff and students - directed towards a sustainable development in the institution.